Critical thinking skills for education students - Eales-Reynolds, Lesley-Jane; Judge, Brenda; Jones, Patrick; McCreery, Elaine (London SAGE/Learning Matters, 2013)
This title will help education students develop their understanding of critical analysis. It outlines the skills needed to examine and challenge data and encourages an appreciation of how this way of thinking can enrich the personal and professional development of students.
Critical thinking: why is it important and what is it anyway? -- Developing a critical mindset: deconstructing argument. -- Information (digital) literacy. -- Analysing data and interpreting findings. -- Developing your critical thinking skills: reading critically. -- Developing critical thinking through writing. -- Analysing your own writing. -- Assessing criticality. -- A critical thinking community. -- Critical thinking in the professional context.
Revised edition of: Critical thinking skills for education students / Brenda Judge. 2009.
Includes bibliographical references and index.
Keywords: Critical thinking -- Study and teaching (Higher) -- Great Britain; Teachers -- Training of -- Great Britain